(untitled) (Bangladesh Journal of Animal Science, 2021)
A 2×3 factorial experiment was conducted to compare two cultivars; Bangladesh Livestock Research Institute developed Napier hybrid-3 (BN-3) (Pennisetum purpureum) and Pakchong-1 (Pennisetum purpureum× P. glaucum) in terms of forage growth, biomass yield, and nutritional quality. Cultivars were cultivated in 03 blocks with 03 replicates and were harvested at 03 cutting periods (40, 50, and 60 days). Plot sizes for each cultivar were 25 m2 (5m × 5m), and in every plot, twenty-five stem cuttings with two healthy nodes per cutting were planted with (1×1) m spacing. The effects of cultivar and cutting period were significant on plant height, leaves per tiller, leaf DM production, and leaf stem ratio (LSR). Highest plant height (P<0.01) and leaves per tiller (P<0.05) were consistently produced by BN-3, while Pakchong-1 produced the highest amount of CP (P<0.05), LSR (P<0.05), tiller diameter (P<0.01) and diameter of the lowest node (P<0.01). Based on the %DM, DM yield, and CP yield, BN-3 performed better cutting at 50 days after the first plantation, but Pakchong-1 performed better cutting at 60 days after the first plantation. From the forage standpoint, Pakchong-1 seems to have little advantages over BN-3 because of its higher DM, LSR, and CP production. Bang. J. Anim. Sci. 2021. 50 (1):43-49